Automatic Control System Application for Melon Growth in Greenhouse Using IoT and Fuzzy Control - Srinil, Phaitoon; Puangsuwan, Thararat; Buatoom, Uraiwan; Kunjet, Sumit (Journal of Science Ladkrabang, 2021)
This research presents a smartphone application for the automatic control of a melon growth in the greenhouse. The development process includes four main parts: greenhouse environmental data observing, fuzzy controller design, smartphone application of control system development, and system performance testing. The fuzzy controller is designed and performed based on the experiment of growing melon in the greenhouse controlled by the agriculture expert. The smartphone application is developed using the Node-RED and IoT technologies. Compared to the melon yields' system performance with the traditional process, statistical results with z-test showed no significant difference in melon yield from both melon's weight and sweetness values at a significance level of 0.05. Hence, this approach can also be applied to monitor the melon's growth in the greenhouse same as a human expert.